MORPHOFUNCTIONAL CHARACTERISTIC OF HEMOMICROCIRCULATORY BED IN THE RED BONE MARROW WHEN MODELING AN ACUTE ASEPTIC INFLAMMATION IN RATS - Boruta, N.V. (World of Medicine and Biology, 2020)
In modern medicine, the structural components in various organs and tissues have been studied in great detail, but at the same time there are no works which would study hemomicrocirculation in the red bone marrow in the modeling of acute aseptic inflammation in rats, where reactive changes of morphological and functional character take place. The purpose of the work was to study the morphological changes of the components of the hemomicrocirculatory bed in the red bone mrrow of rats when modeling an acute aseptic inflammation. The work was performed on 50 mongrel white rats, divided into 2 groups: Group I–5 intact animals, Group II included 45 animals, which were simulated an acute aseptic peritonitis. In experimental groups of animal, an immediate, but reversible, increase in the penetration of venules and capillaries was observed, due to the active reduction of microfilaments in endothelial cells. In vascular lumens, during the experiment, a sludge syndrome was observed, which led to the difficulty of perfusion of blood corpuscles through the wall of the venule, which is a morphological confirmation of the inflammatory process.